Short-term impacts of mergers and acquisitions on acquiring firm’s value - Jokinen, Jani (2020)
The objective of this study is to explore Finland's most significant cross-border acquisitions and their short-term impact on acquiring the company's share price during the years of 1997-2019. Secondly, the study explores whether the cash payment method affects the short-term performance of Finnish cross-border acquisitions. The study consists of 40 publicly listed Finnish firms that entered cross-border acquisitions exceeding a deal value of 500 million US dollars. The research was conducted with an event study methodology, which explains the announcement effect of M&A on acquiring the company's share prices. The study focuses on whether Finnish cross-border acquisitions increase or decrease the value of the acquiring company's shareholders. Value creation or destruction is analysed with abnormal and cumulative abnormal returns within the event window. AAR and CAAR results were analysed ten days before and nine days after the announcement. The first result shows evidence that Finland's most significant cross-border acquisitions do not create value for the acquiring company's shareholders; instead, it has slightly value destructive effect in the short-run. The result is not consistent with the assumption that the acquisitions are motivated by synergy advantages. Consequently, my results argue for managerial hubris and overestimated synergy advantages' existence. This result is aligned with earlier empirical literature, which argues that more significant M&A transactions can quickly pay too high a premium, consequently destroying the value of the acquiring companies` shareholders. The second result provides evidence that the cash payment method generates positive and significant cumulative abnormal returns during the whole event window period. This gives evidence that value is created for the acquiring company's shareholders in the short run. The cash payment method contributes to synergy advantages. Earlier empirical evidence argues that rational managers do not misevaluate cash offerings, which advocates my results.